La matière féerique dans Salammbô - Gesine Hindemith (Flaubert: Revue Critique et Génétique, 2014)
This article approaches Flaubert’s historical novel Salammbô from the perspective of fantasy. We postulate that Flaubert, who was highly inspired by this popular theatrical genre, takes fantasy as a model for his deconstruction of the writing of History. On the one hand he establishes a certain discontinuity through a structure of pictures, and on the other, he uses visual effects existing in the fantasies of that period, in particular apparitions and disappearances. Flaubert’s almost cinematographic technique, which literary research has lately identified, owes much to fantasy, a genre that was considerably in fashion at the time. Through these visual and structural techniques the writer stages the ambivalence between the magical and the catastrophic, characteristic of fantasy. Thus the Punic Wars Carthage is fossilized, as a time stratum doomed to disaster and annihilation.